Understanding case mix across three paediatric services: could integration of primary and secondary general paediatrics alter walk-in emergency attendances?. Issue 5 (16th May 2019) - Steele, Lloyd; Coote, Nicky; Klaber, Robert; Watson, Mando; Coren, Michael
Abstract : Objective: To understand the case mix of three different paediatric services, reasons for using an acute paediatric service in a region of developing integrated care and where acute attendances could alternatively have been managed. Methods: Mixed methods service evaluation, including retrospective review of referrals to general paediatric outpatients (n=534) and a virtual integrated service (email advice line) (n=474), as well as a prospective survey of paediatric ambulatory unit (PAU) attendees (n=95) and review by a paediatric consultant/registrar to decide where these cases could alternatively have been managed. Results: The case mix of outpatient referrals and the email advice line was similar, but the case mix for PAU was more acute. The most common parental reasons for attending PAU were referral by a community health professional (27.2%), not being able to get a general practitioner (GP) appointment when desired (21.7%), wanting to avoid accident and emergency (17.4%) and wanting specialist paediatric input (14.1%). More than half of PAU presentations were deemed most appropriate for community management by a GP or midwife. The proportion of cases suitable for community management varied by the reason for attendance, with it highestl for parents reporting not being able to get a GP appointment (85%), and lowest for those referred by community health professionals (29%). Conclusions: One in two attendances to acute paediatric services could have been managed in the community. Integration of paediatric services could help address parental reasons for attending acute services, as well as facilitating the community management of chronic conditions.